PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI UTD PMI KOTA MALANG - Aliyah Rahmawati (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2022)
Developments in the current era, especially during the Covid-19 pandemic where companies are expected to have agility, require companies to continue to develop and make appropriate strategic decisions. This study aims to examine the effect of intellectual intelligence, emotional intelligence and spiritual intelligence on employee performance by adding the intervening variable, namely job satisfaction. Respondents are employees of UTD PMI Malang City, amounting to 84 people using a saturated sample. The research method uses quantitative descriptive, data analysis using SPSS software version 20. This research shows that 1). Intellectual intelligence has no significant effect on performance through job satisfaction as an intervening variable, 2). Emotional intelligence has a significant effect on performance through job satisfaction as an intervening variable, 3). Spiritual intelligence has no significant effect on performance through job satisfaction as an intervening variable.